Prognostic Value of Arm Circumference for Cardiac Damage and Major Adverse Cardiovascular Events: A Friend or a Foe? A 2-Year Follow-Up in the Northern Shanghai Study - Zheng, Yixing; Zhang, Ji; Ren, Zhongyuan; Meng, Weilun; Tang, Jiamin; Zhao, Song; Chi, Chen; Xiong, Jing; Teliewubai, Jiadela; Maimaitiaili, Rusitanmujiang; Xu, Yawei; Zhang, Yi (Frontiers in Cardiovascular Medicine, 2022)
Background Globally, the prevalence of cardiovascular diseases has caused great social burden and individual suffering. The efficient identification of high-risk population is the critical task in primary prevention. Anthropometric characters, which are facile and low-cost, are commonly applied for general population. However, considering the global social aging, the anthropometric characters in the elderly might have different prognostic value. Our study aimed to find a convincing anthropometric character as the supplement to conventional risk factors of major adverse cardiovascular event (MACE) in the elderly. Materials and methods 1576 elderly participants (44.5% male, aged 72.0±6.0 years) recruited into the Northern Shanghai Study 2014-2015 were followed up between 2016 and 2017. Following the standard guideline, cardiovascular risk evaluation and organ damage (OD) including cardiac, vascular, and renal damage were assessed. The body measures were made up of body weight, body height, hip circumference, waist circumference and middle-upper arm circumference (MUAC). Results After the average 571（±135）days of follow-up, a total of 90 MACE (5.7%) occurred including 13 non-fatal myocardial infarction，68 non-fatal stroke and 9 cardiovascular deaths. Univariable COX survival analysis revealed that only MUAC could validly predict MACE among anthropometric characters (adjusted hazard ratio (HR) 0.89; 95% Confidence Interval (CI) 0.82-0.96). In Kaplan-Meier analysis, the group of high MUAC showed the lowest MACE risk (Log-Rank p=0.01). Based on OD analysis, MUAC was independently tied to higher risk of left ventricular hypertrophy (LVH) in females and left ventricular diastolic dysfunction (LVDD) in both males and females. In adjusted COX analysis, only MUAC indicated statistical significance except, other all anthropometric parameters including BMI, waist circumference and waist-to-hip ratio (WHR) didn’t. The higher level of MUAC remained a protective factor in fully adjusted models (HR 0.73; 95% CI 0.59-0.91).After taking account of all factors (cardiovascular risk factors, MUAC, BMI and WHR), the fully adjusted COX regression analysis demonstrated that increased MUAC level was tied to decreased MACE risk in both male (HR:0.57; 95% CI: 0.37-0.88) and female (aHR:0.64; 95% CI: 0.46-0.93). Conclusion Although associated with higher rate of cardiac damage, higher MUAC independently and significantly conferred protection against MACE, in the elderly cohort.